Draft Annual Plan 1981-82 Tamil Nadu Narrative Notes on Programmes - Planning Commission (Planning Commission, 1981)
In the year under review, the Agriculture sector achieved an all-time high level of foodgrain production. To an extent this had a favourable impact on industrial production and the general price level, as well as State Income. Industrial product! on, on the other hand, registered an unimpressive growth owing to obstacles in power supply and raw materials shortages, and to a small extent problems in labour management. However, indications are that in recent months industrial production has begun to improve. The power front was less efficient this year contributed by deficiencies in thermal power, giving cause for a fairly long period of varying degrees of power cuts. The step-down in relief from outside had sizeably reduced power avaialability in the State. The uptrend in prices was mainly influenced by the manufacturing sector. In the vital sphere of employment, the backlog of registered unemployed kept pace with job creation at higher levels from year to year. The State economy’s progress was amidst pressures of different kinds and future prospects would depend on the extent the pressures are eased.
Planning and Development Department Government of Tamil Nadu